Effectiveness of Gamified Learning Strategies in Secondary Education - Purwanti, Rina; Akhtar, Shazia; Mokoena, Lesedi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Gamified learning strategies have gained popularity in secondary education as a method to boost student engagement, motivation, and learning outcomes. In an era where technology and interactivity increasingly shape educational environments, gamification offers a unique approach by integrating game elements like points, badges, and leaderboards into the learning process. This research aims to assess the effectiveness of gamified learning strategies in improving academic performance, engagement, and motivation among secondary school students. A quasi-experimental design was used, involving two groups of students from three secondary schools: one utilizing a gamified learning approach and the other following traditional teaching methods. Data was collected through pre- and post-tests, engagement surveys, and interviews, allowing for both quantitative and qualitative analysis. The results showed that students in the gamified group demonstrated a 25% improvement in test scores and reported higher levels of engagement and motivation compared to the control group. The study concludes that gamified learning strategies can significantly enhance learning outcomes and student involvement in secondary education. These findings suggest that integrating game-based elements into curricula may create a more interactive and motivating learning environment, supporting academic growth. Further research is recommended to explore the long-term effects of gamification and its applicability across different subjects and educational levels.